1998
DOI: 10.1038/sj.bjp.0702066
|View full text |Cite
|
Sign up to set email alerts
|

Actions of novel antidiabetic thiazolidinedione, T‐174, in animal models of non‐insulin‐dependent diabetes mellitus (NIDDM) and in cultured muscle cells

Abstract: 1 The antihyperglycaemic e ect and the possible mechanism of action of T-174, a novel thiazolidinedione derivative, was determined in vivo and in vitro. 2 Oral administration of T-174 markedly improved hyperglycaemia, hyperinsulinaemia, hyperlipidaemia, and glucose intolerance in genetically obese and diabetic yellow KK (KK-A y ) mice (0.2 ± 15.5 mg kg 71 day 71 , for 7 days) and Zucker fatty rats (1.4 ± 11.4 mg kg 71 day 71 , for 6 days). The ED 50 values for the glucose lowering action of T-174 and pioglitaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…None of these defects were influenced by metformin treatment. There are reports of thiazolidinediones improving adipocyte glucose uptake and GLUT4 expression in various animal models of insulin resistance (38,39), results that mirror the current findings in human adipocytes and suggest that the effects are general to the class of thiazolidinediones and not specific for troglitazone.…”
Section: Discussionsupporting
confidence: 70%
“…None of these defects were influenced by metformin treatment. There are reports of thiazolidinediones improving adipocyte glucose uptake and GLUT4 expression in various animal models of insulin resistance (38,39), results that mirror the current findings in human adipocytes and suggest that the effects are general to the class of thiazolidinediones and not specific for troglitazone.…”
Section: Discussionsupporting
confidence: 70%
“…Rapid stimulation of lactate release by 20 I nsulin resistance is a common metabolic abnormality associated with obesity, hypertension, and type 2 diabetes (1). Thiazolidinediones (TZDs) are a class of oral antidiabetic agents that improve insulin sensitivity and glucose homeostasis in type 2 diabetic patients (2-4) as well as in various animal models of diabetes and obesity (2)(3)(4)(5)(6)(7)(8)(9). The TZDs troglitazone, rosiglitazone, and pioglitazone have already been used in clinical practice, but the mechanisms by which TZDs improve insulin sensitivity as well as deranged glucose and lipid metabolism are not yet fully understood (2)(3)(4)10).…”
mentioning
confidence: 99%
“…In many studies, TZDs were found to stimulate glucose transport into skeletal muscle in vitro [16,70,111,112,113,114,115,116,117,118,119,120] but the accompanying changes in intracellular glucose fluxes were rather inconsistent, ranging from stimulation to inhibition of both glucose oxidation and glycogen synthesis [16,70,111,112,113,114,121]. The heterogeneity of effects on intracellular glucose routing is obviously related to the diversity in experimental settings.…”
Section: Skeletal Musclementioning
confidence: 99%
“…The most important observation supporting a causal interdependence between TZD-induced PPARγ activation and the improvement of glucose homeostasis is the association of PPARγ agonistic activity in vitro with antidiabetic action in vivo, which characterizes numerous TZDs [16,37,69,70,71,72], and also non-TZD PPARγ agonists belonging to the classes of isoxazolidinediones [73,74], tyrosine derivatives [75,76,77], and phenylacetic or phenoxyacetic acid derivatives [37]. Although the maximal antihyperglycaemic potentials of many TZDs and other PPARγ agonists are similar, oral dose requirements for half-maximal glucose lowering in diabetic mice differ considerably and correlate strongly with PPARγ binding activities and transactivating potentials of the respective compound in vitro [37, 69,71].…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation